SKRINING AKTIVITAS ANTI Escherichia coli ATCC 25922 EKSTRAK METANOL DARI BEBERAPA TANAMAN RIMPANG - Alma Yulvita Pebriana; Eva Marliana; Ritbey Ruga (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Antibacterial activity from methanol extracts of edible rhizomes namely temu putih (Curcuma zedoaria), temu ireng (Curcuma aeruginosis), temu giring (Curcuma heyneana) and temu kunci (Boesenbergia pandurata) against Escherichia coli ATCC 25922 based on diameter of inhibition zone by using agar difusion method was conducted. With 1% of each extracts, methanol extract of temu kunci showed excellence acntibacterial acitivty against E. coli with the diameter of inhibition zone of 20,0 mm and followed by methanol extract temu giring is 19,0 mm. While methanol extract of temu ireng and temu putih revealed strong antibacterial activity with inhibition zones of 10.7 and 10,0 mm, respectively. Keywords: Methanol Extract, Antibacterial, Escherichia coli